Effect of Water Availability on the Growth and Secondary Metabolites of Zodia (Evodia suaveolens) - Setyawati, Andriyana; Purwanto, Edi; Yunus, Ahmad; Samanhudi, Samanhudi; Sakya, Amalia Tetrani; Rahayu, Muji; Purnomo, Djoko; Arniputri, Retna Bandriyati; Cahyo, Gani; Dwiyanti, Qonita Rahma; Egra, Saat; Talitha, Okky; Muthi’ah, Alfida (Universitas Sebelas Maret, 2023)
Zodia are included in medicinal plants because it contains secondary metabolites such as flavonoids, tannins, alkaloids, steroids/triterpenoids that have many benefit and also as mosquito repellents. The growth and content of secondary metabolites in plants can be affected by environmental factors such as water availability. Research on the cultivation of this crop is still limited. Environmental modification in cultivation is needed to increase its secondary metabolites, and the study of the potential of this plant as medicine are necessary. This study aimed to determine the effect of water availability on the growth and secondary metabolites of zodia. The research was carried out in July-November 2021 in Greenhouse, Faculty of Agriculture, Universitas Sebelas Maret, Surakarta. The method used was a completely randomized design, one treatment factor with 4 levels namely, 100, 80, 60 and 40% of field capacity. Each treatment was repeated 6 times so that there were 24 experimental polybags. The data analysis used is Analysis of Variance, and the Duncan’s Multiple Range Test at the 5% level. The results showed that the availability of water at a level of 60% field capacity gave the best average growth parameters (plant height and number of leaves) among other treatments. The flavonoid content in each treatment showed the same average. The results of the GCMS (Gas Cromatography and Mass Spectroscopy) test of zodia leaves showed that there were dominant bioactive compounds, namely ethylbenzene, octadecamethyl cyclononasiloxane, pentadecanoid acid and heptadecanoid acid. It is suspected that the content of these compounds has the potential as antifungal, antibacterial, antioxidant and anticancer.